2003
DOI: 10.1111/j.1365-2621.2003.tb08263.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dielectric Properties of Ham as a Function of Temperature and Composition

Abstract: The dielectric properties of 19 different ham samples with different moisture (38.2% to 68.9%) and ash contents (1.78% to 6.80%) were measured at -35 to 70 °C at 2450MHz. Equations were developed as a function of temperature, moisture, and ash, and compared to literature equations. The dielectric constant decreased with ash content and increased with moisture content. It increased instead of decreasing with temperature. The dielectric loss factor increased with moisture content for moisture contents lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
(18 reference statements)
2
17
1
3
Order By: Relevance
“…Dielectric properties, namely, dielectric constant and loss factor values, have previously been studied by Sipahioglu et al [8], Ryynänen [27], and Lizhi et al [28] and this study has shown similar trend for all three fruits. Dielectric constants for all three fruits are plotted in Figure 3 ∘ C) for papaya, all at 0.001 MHz, which decreased by 2.8, 2.68, and 14.07 times when 0.1 MHz was reached.…”
Section: Frequency Dependence Of Dielectric Propertiessupporting
confidence: 67%
See 1 more Smart Citation
“…Dielectric properties, namely, dielectric constant and loss factor values, have previously been studied by Sipahioglu et al [8], Ryynänen [27], and Lizhi et al [28] and this study has shown similar trend for all three fruits. Dielectric constants for all three fruits are plotted in Figure 3 ∘ C) for papaya, all at 0.001 MHz, which decreased by 2.8, 2.68, and 14.07 times when 0.1 MHz was reached.…”
Section: Frequency Dependence Of Dielectric Propertiessupporting
confidence: 67%
“…A lot of work has been done for studying the electrical and dielectric properties of various food items and food ingredients at microwave frequencies by Sipahioglu and Barringer [7], Sipahioglu et al [8], Soltani et al [9], Sharma and Prasad [10], and many others, but there is no significant amount of work on the study of these properties for tropical fruits at very low frequency levels (0.001 MHz to 10 MHz). Li et al [11] measured moisture content of cookies using dielectric spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Los autores desarrollaron ecuaciones para correlacionar la parte real e imaginaria de la permitividad con la temperatura, humedad, actividad de agua y cenizas. Otras ecuaciones se desarrollaron para modelizar las propiedades dieléctricas del jamón en función de la temperatura y la composición (Sipahioglu et al, 2003a). Por otra parte, el mismo grupo de investigación estudió el efecto de la adición de ácido láctico en carne de pavo (Sipahioglu, 2002) a frecuencias de 915 y 2450 MHz.…”
unclassified
“…En este sentido se han realizado numerosos estudios en alimentos (Van Dyke et al, 1969;Roebuck et al, 1972;To et al, 1974;Nelson, 1978a,b;Mudgett et al, 1980;Padua, 1993;Tulasidas et al, 1995;Bircan y Barringer, 1998;Funebo y Ohlsson, 1999;Kraszewski, 2000;Sipahioglu, 2002).…”
unclassified
See 1 more Smart Citation